ANALISIS MANFAAT PELAYANAN HAI-CSO PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA MEULABOH - Zahara Phonna; Fatmayanti Fatmayanti; Daniel Santuri (Jurnal Sains Riset, 2022)
This study aims to determine the benefits of the help, answer, improve – Costumer Service Officer service at the Meulaboh State Treasury Office. Whether the service provides accurate, intergated, and timely information, then whether the service answer question form the appropiate work unit for them. Want. The research method user is descriptive whit a narrative approach. Data collection techniques using retrieval from documents and direct  interview techniquest from one of the employees of KPPN Meulaboh. The population in this study were all users oh the HAI-CSO service who managed the finances of the work units whithin the working area of the Meulaboh KPPN. The results of this study indicate that the questions posed by the work unit have several unanswered tickets, the quality of the answers provided by the KPPN fulfills the wishes of the work unit, and the HAI-CSO service facility is very useful and utilized by the work unit to obtain information as needed.Keywords : HAI-CSO, Sevice Quality, Service